2002
DOI: 10.1007/bf03345102
|View full text |Cite
|
Sign up to set email alerts
|

GH-IGF-I axis in non-obese women with functional hyperandrogenism

Abstract: The study was conducted to assess the GH-IGF-I axis in non-obese women with functional hyperandrogenism (FH). Eighteen FH women aged 18-35 yr with a body weight within 20% of ideal body weight and 10 weight-matched controls were included in the study. Basal serum GH, GH-binding protein (GHBP), IGF-I, IGF-binding protein-3 (IGFBP-3) levels were determined as well as GH levels during GHRH stimulation. In addition, basal serum androgens [free T (FT), delta4 and DHEAS], insulin and glucose levels were determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Furthermore, it has also been reported that serum DHEA levels correlate positively with GH and IGF-I levels in nonobese women with functional hyperandrogenism (Legan et al 2002), in pubertal development, and in aging (Shealy 1995, Kroboth et al 1999. DHEA replacement in old healthy people as well as in patients with primary adrenal insufficiency produced an increase in serum IGF-I (Arlt et al 1999).…”
mentioning
confidence: 92%
“…Furthermore, it has also been reported that serum DHEA levels correlate positively with GH and IGF-I levels in nonobese women with functional hyperandrogenism (Legan et al 2002), in pubertal development, and in aging (Shealy 1995, Kroboth et al 1999. DHEA replacement in old healthy people as well as in patients with primary adrenal insufficiency produced an increase in serum IGF-I (Arlt et al 1999).…”
mentioning
confidence: 92%